The Correlation Between Student Participation and Student Motivation Toward Student English Achievement at Senior High School - Purmadhani, Agithania; Muniroh, Siti; Khoiri, Niamika El (Universitas Negeri Malang, 2024)
Student participation and student motivation are pivotal efforts to optimize student learning outcomes, particularly in English achievement. This research aimed to ascertain the correlation between student participation (X1) and student motivation (X2) with English achievement (Y) among the twelfth science 3 graders of SMA Negeri 4 Malang. Employing a quantitative approach with a correlational research design, the study quantitatively describes the extent to which these variables are related. The subjects of this research comprised 32 students. Data collection was conducted using a questionnaire and student achievement documentation. The data analysis utilized the Azwar 2012 formula and the SPSS 23 version software. The results indicated that the F achievement value was 3.470, while the F table value at n=29 with a significance error of 0.05 was 3.33. This finding suggests that the F achievement value is higher than the F table value (F achievement > F table), leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). Thus, the research concludes that student participation and motivation significantly contribute to improving students' English achievement. Furthermore, this study highlights the importance of fostering an engaging and motivating classroom environment to enhance students' language skills. Active student participation not only reflects their interest in the subject matter but also encourages a more dynamic and interactive learning process. Similarly, motivation serves as a driving force that propels students to strive for better performance and achievement. By understanding and leveraging these factors, educators can implement strategies that better support students' academic growth and proficiency in English. This research provides valuable insights for educational practitioners aiming to improve English learning outcomes through targeted interventions that boost student engagement and motivation.